Participação privada na investigação criminal no Brasil : possibilidades e limites - França, Rafael Francisco (2014)
This paper has as its objective to analyze the possibility of private participation in the Brazilian criminal investigation, which is enfolded into the mandatory and official state procedural actions. Therefore, the research ensues from the study of the fundamental rights to establish the existence of the right to law enforcement and investigative action to be executed by the state. Such intervention should be developed through procedures and institutions created and maintained by the state, which also determines the need for private investigative action in the absence or inefficiency of the official criminal investigation. The work is based on the right to investigative action resulting from the duty to provide protection, as a means to allow private participation in the investigation of crimes, which are also analyzed by the decisions of international courts of human rights that make use of similar paths to determine the need for preliminary criminal investigation as a means to protect fundamental rights. Furthermore, are exposed limits as to who investigates and how that can be produced by private participation.